2009
DOI: 10.1590/s0100-736x2009000700008
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a gE-deleted, bovine herpesvirus 1 (BoHV-1) inactivated vaccine

Abstract: Pesq. Vet. Bras. 29(7): 545-551, julho 2009 RESUMO.-[Eficácia de uma vacina inativada, gE-deletada, contra o herpesvírus bovino tipo 1 (BoHV-1).] O Herpesvírus bovino tipo 1 (BoHV-1) é reconhecido como um importante agente de perdas econômicas em bovinos. Vacinação tem sido amplamente empregada para minimizar as perdas conseqüentes a infecções com o BoHV-1. Reportamos previamente o desenvolvimento de uma vacina diferencial para BoHV-1, baseada em um recombinante do qual a glicoproteína gE (gE) foi deletada … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…The reaction was developed by incubation with peroxidase‐labeled anti‐IgY and a final step of adding 0.03 % H 2 O 2 and 1 mg/ml o‐phenylenediamine. The specificity of chicken positive sample (cut off) was arbitrarily defined as 2× the OD value of the negative serum .…”
Section: Methodssupporting
confidence: 53%
“…The reaction was developed by incubation with peroxidase‐labeled anti‐IgY and a final step of adding 0.03 % H 2 O 2 and 1 mg/ml o‐phenylenediamine. The specificity of chicken positive sample (cut off) was arbitrarily defined as 2× the OD value of the negative serum .…”
Section: Methodssupporting
confidence: 53%
“…The serum neutralization (SN) test used to quantify BoHV-1 neutralizing antibodies in sera of cattle is recommended by the World Organization for Animal Health (OIE). SN has been used extensively to evaluate vaccines [ 11 , 12 , 13 , 14 ], although there is a difference in the titers obtained according to the sample used [ 15 ]. Moreover, it has been shown that the efficacy of the immune response against BoHV-1 depends on increased Th1-type cell-mediated responses [ 16 ].…”
Section: Introductionmentioning
confidence: 99%